Prevalência de perda auditiva em bebês de alto risco - Fernanda Alves Botelho (2009)
Background: hearing loss may start before the acquisition of language and harm its development, in addition to influencing cognitive and social function. Objective: to assess the prevalence of hearing loss in newborns with risk indicators born and followed in the Hospital das Clinicas da UFMG from June 2006 to July 2008. To correlate the possible variables related to hearing loss. Methods: we evaluated 188 newborns and collected the data from the patient history through interviews with the parents and review of medical records. The Evoked Otoacoustic Emissions by Distortion Product was examined hearing behavior observed. When changes occurred since the first examination the test was repeated at the next pediatric consultation. In cases where the changes persisted, the child was referred for evaluation of the external and middle ear through the acoustic impedance, and when necessary to medical evaluate. It was reviewed after medical intervention. Thosethat had not shown conductive change were evaluated through the Brainstem Auditory Evoked Potential. Results: Among the 188 children evaluated, two (1.1%) were excluded because the results could not be determined by the end of data collection. 174 (92.6%) showed audiological assessment scores within the normal range.We found 12 children with hearing impairment, which represents 6.3% of the population studied, and in 3 these the deficit were retro cochlear. It was found that the unilateral hearing impairment occurred in 2 children and in 10 the deficit was bilateral. Conclusion: It is known that the hearingscreening programs in Brazil are poor. In order to raise awareness of the impact of deafness on child development further studies are necessary to promote change of the high prevalence of hearing loss.